UJI PERTUMBUHAN DAN HASIL TANAMAN SAWI HIJAU (Brassica juncea L.) MELALUI TAKARAN BIOCHAR SEKAM PADI DAN WAKTU APLIKASI LIMBAH CAIR TAHU - Bria, Deseriana; Neonbeni, Eduardus Yosef; Kehi, Stefanus (Agriculture Faculty of Flores University, 2025)
Mustard greens (Brassica juncea L.) are a vegetable crop that is popular with many people but is experiencing a decline in production. Mustard greens (Brassica juncea L.) are a vegetable crop that is popular with many people but is experiencing a decline in production. This problem is caused by a lack of water, less intensive cultivation techniques and a decrease in soil fertility. This research was carried out with the aim of finding out the effect of the rice husk biochar dosage and the optimal application time for tofu liquid waste to increase the growth and yield of the Tosakan F1 variety of green mustard greens. The research was carried out from June to July 2023 at the Faculty of Agriculture, University of Timor, Sasi Village, South Bikomi District, North Central Timor Regency. The polybag experiment was arranged according to a 3 x 3 factorial completely randomized design (CRD) which was repeated 3 times, consisting of 2 factors, namely: the first factor was the dose of rice husk biochar, namely; without biochar, rice husk biochar dosage (7%), rice husk biochar dosage (14%). Meanwhile, the second factor is the application time for tofu liquid waste, namely: without time limit, once every 6 days, once every 12 days, which is repeated 3 times so that there are 27 experimental unit. The results of the research showed that there was an interaction between the 7% rice husk biochar treatment and the application of tofu liquid waste once every 12 days on the leaf number parameter of 21 HST. A dose of 7% rice husk biochar can increase the growth and yield of mustard greens, namely the parameters of plant height (24.00 cm), number of leaves (16.00), leaf area (690.90 cm2), plant fresh weight (75.99 grams). ) and harvest index (87.81%). Application of tofu liquid waste once every 12 days can increase plant height (22.88cm), number of leaves (15.00 pieces), leaf area (691.33 cm2), plant fresh weight (76.35 grams), and harvest index (88.74 %).